PENGARUH METODE BERMAIN PERAN DAN KECERDASAN EMOSIONAL TERHADAP KETERAMPILAN BERCERITA SISWA KELAS VII SMP NEGERI - Ekasari, Arifah Nian; Andayani, Andayani; Slamet, St. Y. (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This research has aims to find out: (1) is there  is any difference between the storytelling skills of the students taught by the role playing method and expository method; (2) is there any difference between the storytelling skills of students who have high emotional intelligence and  low emotional intelligence; and (3) is  there an interaction between the learning method and the emotional intelligence toward storytelling skills.This research method used is a 2x2 factorial design experimental method. The study took a subpopulation which has an equality  curriculum in 2013 were applied. The sample taken are consists of three state schools for experimental class, control class, and instrument class. The technique used in analyzing the research data is the Variance Analysis Technique (Anava) two ways. Based on the research findings, the writer can conclude as follows: (1) there is a difference between storytelling skills of the students taught by the role playing method  and by an expository method; (2) there is a difference between the storytelling skills of students who have high emotional intelligence and low emotional intelligence; and (3) there is no interaction between learning method and emotional intelligence toward storytelling skills.